EVALUASI KEBIJAKAN PENGELOLAAN SAMPAH PADA KECAMATAN DI KOTA DUMAI (STUDI PASCA PELIMPAHAN KEWENANGAN WALIKOTA KEPADA KECAMATAN DIBIDANG PERSAMPAHAN) - Hildawati Hildawati (UIR Press, 2018)
Garbage Problems in Dumai City in Manage by Dumai City Environmental Agency. However, until now the waste problem remains one of the discourses of the City Government to be resolved soon. In 2012, to address the garbage problem, has been issued Mayor Regulation No. 24 of 2012 on the Delegation of the Mayor's Authority to the Sub-District in the Field of Garbage. This is done so that the sub-districts can directly cooperate with relevant institutions to overcome this problem. This research was conducted by survey (field research) with data collection technique that is observation and interview. From the research results found that in the waste management in Dumai City is still Lack of coordination with related agencies such as Dumai City Environmental Office in the division of work areas related to the collection of levies, the absence of technical guidelines as well as guidelines and guidance execution delegation of affairs, the lack of facilities and infrastructure that can support the implementation of the authority overlapping, There are still many complaints to the Dumai City government to overcome this problem but still not overcome.